After-Hours Care in Suburban Canada - David Jones MSc; Linda Carroll PhD; Leonard Frank MSc (SAGE Publishing, 2011)
Objective : To determine if operation of an outpatient "after-hours" clinic (AHC) was associated with a reduction in local emergency department (ED) visits. Study Setting : Leduc, Alberta, Canada is a city of approximately 20 000 people. There is one hospital ED and a single AHC. Information on AHC and ED visits was collected from January 2005 to February 2008. Study Design : This was an observational before-and-after study of monthly ED visit frequency, stratified by patient illness severity. Data Collection : We collected patient visits per month to the ED before and after AHC implementation. Twenty-eight months of ED patient visit information were collected (14 months of pre-AHC; 14 months of post-AHC). A Wilcoxon signed-rank test was used to test the statistical strength of difference in ED visits, matched by month, before and after the AHC became operational. Results : An average of 261.2 (standard deviation [SD], 47.7) patient visits per month were made to the AHC. There was a mean reduction of 36.7 (standard error of mean [SEM], 9.6; P = .009) total patient visits per month and 49.3 (SEM, 5.6; P = .001) fewer semiurgent patient visits per month to the Leduc ED during AHC operating hours. Conclusions : There was a consistently observable and statistically significant reduction in total patients visiting the ED subsequent to AHC operation. Stratified analysis indicated that this was due to fewer semiurgent patients seeking medical care at the local ED.